Validity of e-handout diversity bacterial colonies in rhizosphere Citrus nobilis at Karang Bunga Agrotourism Barito Kuala - Annisa Fujianti; Aulia Ajizah; Noorhidayati Noorhidayati (HAFECS PRESS, 2024)
Digital handouts, or e-handouts, are learning tools students can use to learn more efficiently and flexibly. This study aimed to assess the validity of e-handouts on bacterial diversity in the rhizosphere of Citrus nobilis as Microbiology enrichment material. This research uses the Research and Development (R&D) method with the ADDIE model, which is limited to the development stage. The subjects in the study consisted of validation tests by three validators, namely material experts. As many as two people are lecturers in the Microbiology and Plant Physiology Course of Biology Education FKIP ULM Banjarmasin and one media expert from a lecturer in Educational Technology FKIP ULM Banjarmasin. In the e-handout validation test, the material validator was rated as very valid with a percentage of 86.15%, and the developed media validator showed the e-handout was very valid with a percentage of 100%. It can be concluded that the e-handout of bacterial colony diversity in the rhizosphere of Citrus nobilis meets the category of very valid, and suggestions for further research can be carried out until the product implementation stage. Abstrak. Handout digital, juga dikenal sebagai e-handout, adalah alat pembelajaran yang dapat digunakan siswa untuk belajar agar lebih efisien dan fleksibel. Tujuan dari penelitian ini untuk menilai kevalidan e-handout tentang keragaman bakteri yang ada di rizosfer Citrus nobilis sebagai bahan pengayaan Mikrobiologi. Penelitian ini menggunakan metode Penelitian dan Pengembangan (R&D) dengan model ADDIE yang dibatasi sampai tahap pengembangan (development). Subjek pada penelitian terdiri dari uji validasi oleh 3 orang validator, yakni ahli materi sebanyak 2 orang yang merupakan dosen Pengampu Mata Kuliah Mikrobiologi dan Fisiologi Tumbuhan Pendidikan Biologi FKIP ULM Banjarmasin dan 1 ahli media dari dosen Teknologi Pendidikan FKIP ULM Banjarmasin. Pada uji validasi e-handout oleh validator materi dinilai sangat valid dengan persentase sebesar 86,15%, dan validator media yang dikembangkan menunjukkan e-handout sangat valid dengan persentase 100%. Dapat disimpulkan bahwa e-handout keragaman koloni bakteri pada rizosfer Citrus nobilis memenuhi kategori sangat valid dan saran untuk penelitian selanjutnya bisa dilakukan sampai tahap implementasi produk.